Scintillating Catch Phrases in Selected Presidential End of Year Speeches in Cameroon - Nji, Joefrey Ngha Fuh (Advances in Social Sciences Research Journal, 2025)
This study explores scintillating catch phrases in selected presidential end of year speeches in Cameroon. The study investigates how scintillating catchphrases have been used by the president during his end of year speeches. The paper argues that he wants to capture the attention of the audience and convince them to believe in his discourse, so the citizens can continue to support him and his political ideology and to maintain self in power. The analysis will bother on some selected speeches which the paper finds necessary to meet the objective of the research. The data is collected from Cameroon Tribune the state bilingual daily newspaper which publishes the end of year speeches in both French and English. Only the English versions have been used in the work. The theoretical framework that has informed this research is Critical Discourse Analysis drawing largely on Ruth Wodak’s Discourse Historical Approach (DHA) 2009, and Teun van Dijk’s Socio-Cognitive Approach (SCA), which opines ‘that properties of language which can vary as a function of social power should be taken into account when analyzing language’ (Van Dijk, 2009). For the DHA, language is not independently powerful-it gains power through the use ‘powerful’ individuals make of. (Wodak, 2009). The results reveal that president Paul Biya uses and switches from one catch phrase to the other in order to spur his audience and capture their attention. These catchphrases are used to good effect in order to lay bare his arguments for the development of the country and to better the living conditions of Cameroonians.